2020
DOI: 10.1088/1748-9326/ab6d38
|View full text |Cite
|
Sign up to set email alerts
|

Lichen cover mapping for caribou ranges in interior Alaska and Yukon

Abstract: Previous research indicates that the effects of climate warming, including shrub expansion and increased fire frequency may lead to declining lichen abundance in arctic tundra and northern alpine areas. Lichens are important forage for caribou (Rangifer tarandus), whose populations are declining throughout most of North America. To clarify how lichen cover might affect caribou resource selection, ecologists require better data on the spatial distribution and abundance of lichen. Here, we use a combination of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…Furthermore, our results demonstrate that snow should be included in future analyses, along with a range of other factors documented as being influential for caribou wintering location, e.g., overgrazing of slow-growing lichen species [ 42 , 136 ]. Macander et al [ 108 ] reported that caribou in interior Alaska prefer lichen habitats in winter until they become overgrazed, and consequently, the herd shifts wintering area within the boreal forest region. The CAH winter range variation may be explained by consistent use of winter ranges south of CD from 2001/02 to 2015/16, interrupted only when the very low fall snow depths allowed caribou to winter north of CD in 2007/08 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, our results demonstrate that snow should be included in future analyses, along with a range of other factors documented as being influential for caribou wintering location, e.g., overgrazing of slow-growing lichen species [ 42 , 136 ]. Macander et al [ 108 ] reported that caribou in interior Alaska prefer lichen habitats in winter until they become overgrazed, and consequently, the herd shifts wintering area within the boreal forest region. The CAH winter range variation may be explained by consistent use of winter ranges south of CD from 2001/02 to 2015/16, interrupted only when the very low fall snow depths allowed caribou to winter north of CD in 2007/08 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The wandering nature of caribou is undoubtedly influenced by the snow depths they encounter during winter, but the scattered spatial distribution of lichen [ 108 ] may also contribute to their movement behavior. We found that, irrespective of winter range location, caribou selected for areas with higher lichen proportion than otherwise available in the surrounding landscape, indicating the importance of this winter forage resource (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have indicated that the mapping of caribou lichen is vital for sustainable land management and caribou recovery plans [1][2][3][4][5]. Canadian caribou are threatened by a changing environment due to declining lichen availability, unregulated hunting, habitat disturbances, and herd fragmentation due to human-made infrastructure [2][3][4][5][6]. Lichen is a dominant food source for caribou in the winter, comprising 75% and 25% of their diets in the winter and summer seasons respectively [5].…”
Section: Introductionmentioning
confidence: 99%